Angular Dependence of Fluorescence Emission from Quantum Dots inside a Photonic Crystal. (17th April 2008) - Baert, Kasper; Kolaric, Branko; Libaers, Wim; Vallée, Renaud A. L.; Di Vece, Marcel; Lievens, Peter; Clays, Koen
Abstract : The fluorescence of emitters embedded in a photonic crystal is known to be inhibited by the presence of an incomplete photonic band gap or pseudogap acting in their emission range. Here, we present a study of the angular dependence of the fluorescence emission of emitters embedded in a photonic crystal. Our results clearly show an angular dependence of the fluorescence emission, which is caused by the presence of an incomplete 3D band gap.